Crimes and violence against women in Kyrgyzstan and their aetiology: Przestępczość i przemoc wobec kobiet w Kirgistanie i ich etiologia (Archives of Criminology, 2025)
This paper presents crime and violence against women in contemporary Kyrgyzstan from a criminological point of view. Its purpose is to show the scope and background of these phenomena. It discusses the difficult situation of women resulting from discriminatory and criminal practices on the part of men, such as the kidnapping of women for marriage, early marriage, polygamy and domestic violence. The peculiarities, manifestations and causes of these practices are indicated. It is shown that their extent is closely related to the patriarchal family model that exists to this day in Kyrgyzstan.